Effects of dairy products, calcium and vitamin D on ovarian cancer risk: a meta-analysis of twenty-nine epidemiological studies - Liao, Min-Qi; Gao, Xu-Ping; Yu, Xiao-Xuan; Zeng, Yu-Fei; Li, Shu-Na; Naicker, Nalen; Joseph, Tanya; Cao, Wen-Ting; Liu, Yan-Hua; Zhu, Sui; Chen, Qing-Shan; Yang, Zhi-Cong; et al. (British journal of nutrition, 2020)
Findings for the roles of dairy products, Ca and vitamin D on ovarian cancer risk remain controversial. We aimed to assess these associations by using an updated meta-analysis. Five electronic databases (e.g. PubMed and Embase) were searched from inception to 24 December 2019. Pooled relative risks (RR) with 95 % CI were calculated. A total of twenty-nine case–control or cohort studies were included. For comparisons of the highest v. lowest intakes, higher whole milk intake was associated with increased ovarian cancer risk (RR 1·35; 95 % CI 1·15, 1·59), whereas decreased risks were observed for higher intakes of low-fat milk (RR 0·84; 95 % CI 0·73, 0·96), dietary Ca (RR 0·71; 95 % CI 0·60, 0·84) and dietary vitamin D (RR 0·80; 95 % CI 0·67, 0·95). Additionally, for every 100 g/d increment, increased ovarian cancer risks were found for total dairy products (RR 1·03; 95 % CI 1·01, 1·04) and for whole milk (RR 1·07; 95 % CI 1·03, 1·11); however, decreased risks were found for 100 g/d increased intakes of low-fat milk (RR 0·95; 95 % CI 0·91, 0·99), cheese (RR 0·87; 95 % CI 0·76, 0·98), dietary Ca (RR 0·96; 95 % CI 0·95, 0·98), total Ca (RR 0·98; 95 % CI 0·97, 0·99), dietary vitamin D (RR 0·92; 95 % CI 0·87, 0·97) and increased levels of circulating vitamin D (RR 0·84; 95 % CI 0·72, 0·97). These results show that whole milk intake might contribute to a higher ovarian cancer risk, whereas low-fat milk, dietary Ca and dietary vitamin D might reduce the risk.